Estimation of HIV incidence from analysis of HIV prevalence patterns among female sex workers in Zimbabwe. (1st July 2022) - Ali, M. Sanni; Wit, Mariken D.E.; Chabata, Sungai T.; Magutshwa, Sitholubuhle; Musemburi, Sithembile; Dirawo, Jeffrey; Rice, Brian; Platt, Lucy; Bansi-Matharu, Loveleen; Harriet, Jones; Mharadze, Tendayi; Chiyaka, Tarisai; et al.
Abstract : Objectives: To estimate HIV incidence among female sex workers (FSW) in Zimbabwe: using HIV prevalence by age and number of years since started selling sex (YSSS). Design: We pooled data from FSW aged 18–39 participating in respondent-driven sampling surveys conducted in Zimbabwe between 2011 and 2017. Methods: For each year of age, we estimated: HIV prevalence ( P t ) and the change in HIV prevalence from the previous age ( P t − P t −1 ). We then estimated the rate of new HIV infections during that year of age: I t = P t − P t −1 /(1 − P t −1 ), and calculated HIV incidence for 18–24 and 25–39 year-olds separately as the weighted average of I t . We estimated HIV incidence for FSW 1–5 years and 6–15 years since first selling sex using the same approach, and compared HIV prevalence among FSW first selling sex at their current age with the general population. Results: Among 9906 women, 50.2% were HIV positive. Based on HIV prevalence increases by age, we estimated an HIV incidence of 6.3/100 person-years at risk (pyar) (95% confidence interval [CI] 5.3, 7.6) among 18–24 year-olds, and 3.3/100 pyar (95% CI 1.3, 4.2) among 25–39 year-olds. Based on prevalence increases by YSSS, HIV incidence was 5.3/100 pyar (95% CI 4.3, 8.5) between 1 and 5 years since first selling sex, and 2.1/100 pyar (95% CI −1.3, 7.2) between 6 and 15 years. Conclusions: Our analysis is consistent with very high HIV incidence among FSW in Zimbabwe, especially among those who are young and recently started selling sex. There is a critical need to engage young entrants into sex work in interventions that reduce their HIV risk.